Development of HOTS Ethnomathematics Questions Based on Islamic Values to Enhance Students' Positive Psychology - Selvi Loviana; Ainur Rosidah (Foundation of Jannatun Naim Lampung, 2024)
HOTS questions must be implemented in learning because they refer to cognitive abilities and help students get used to analyzing, evaluating, and synthesizing information. Ethnomathematics HOTS questions still need to be applied in school learning. This study aims to develop HOTS math questions that connect culture with Islamic values, using the traditional Acehnese house as an example of a culture that can be linked with mathematics. The research and development process consists of three stages: analysis, design, and development. This development research results in a product in the form of valid HOTS ethnomathematics questions based on Islamic values that enhance students' positive psychology.